The Use of Recast in the EFL Classroom through Action Research Approach - Bula Villalobos, Olmedo (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2010)
This study reflects upon the experience of using recast as a corrective feedback strategy in an English for specific purposes course for chemists and chemistry students in a university setting. Facilitated by action research, this study reports on how recast in the pre-task and the preparation stage prevent oral errors from happening during the main communicative stage. The effectiveness of recast is also discussed in this paper. One of the main findings is the significance of recasts in the language classroom as a feedback tool.